Vallejo and my Grandpa: Poetic Persona and Real Person in The Black Heralds - Mazzotti, José Antonio (2019)
This paper departs from the personal knowledge that Dr. Humberto Ramos Guardia (Huaraz, December 26, 1900-Lima, October 13, 1980) had of César Vallejo. Dr. Ramos was the maternal grandfather of the author of this essay. He explores the limits between the biographical person of Vallejo and the poetic person represented in his first book, The Black Heralds (1918- 1919). Humberto Ramos Guardia was a science teacher at the Barrós school in the same years that Vallejo was a teacher of History, Language and Geography. Both men cultivated a cordial friendship that allowed Humberto Ramos to get to know closely the jovial personality and mocking ideas of César Vallejo in his Lima stage. The essay will delve into some aspects of The Black Heralds that problematize the traditional image of the depressive and melancholic poet that tends to prevail in the criticism about the poet from Santiago de Chuco.